VERBA GERAKAN AGENTIF DALAM BAHASA DAYAK MALI - Liana Natasia Ersa; Hotma Simanjuntak; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractErsa, Liana Natasia. 2021. The Agentive Movement Verbs in Dayak Mali Language.Thesis. Language and Art Department, Indonesian Language Education StudyProgram, Teacher Training and Education Faculty, Universitas TanjungpuraPontianak. The First Supervisor is Drs. Hotma Simanjuntak, M.Hum., Ph.D. and TheSecond Supervisor is Agus Syahrani, S.Pd. M.M.S.Ling. The title of this research isThe Agentive Movement Verbs in Dayak Mali Language. The general problem in thisstudy was divided into four sub-problems, the first was an inventory of agentivemovement verbs in the Dayak Mali language, the second was the word form of theagentive movement verbs in the Dayak Mali language, the third was a description ofthe meaning of the agentive movement verbs in the Dayak Mali language, and thefourth was the implementation of the learning implementation plan in Senior HighSchool. This study aimed to make an inventory of the agentive movement verb data, todiscover the word form, to discover the lexical meaning of agentive movement verbs,to discover the grammatical meaning of agentive movement verbs, and to implementa lesson plan in Senior High School class XI 2013 curriculum odd semester. Thisresearch used the descriptive method with qualitative study. The source of data wasDayak Mali language spoken by the native speakers in Cowet Village, BalaiSubdistrict, Sanggau Regency, which was represented by three informants. Thetechniques of data collection were one-on-one interview, note-taking, recording, andhooking techniques. The research instruments were voice recorder, questionnaire,notebook, pen. This research discovered 33 agentive movement verbs in Dayak Malilanguage. The word form used in Dayak Mali language was a single word/monofermicwith 22 lexemes, polymofernic consisting of affixation with 2 lexemes, reduplicationwith 2 lexemes, phrases with 7 lexemes, and compounding not found in this study.Based on the agentive movement verbs meaning description, there were 22 lexemesfor the lexical meaning and there were 11 lexemes for the grammatical meaning.Keywords: Agentive Movement Verbs, Dayak Mali Language, Word Form.